The impact of COVID-19 on computed tomography and magnetic resonance imaging exams: A study for the city of Belo Horizonte, Minas Gerais (Research, Society and Development, 2023)
The study of the impacts of COVID-19 pandemic on imaging dynamics is relevant to comprehend the consequences of the sanitary crisis in public health. After all, exams are essential to the adequate diagnosis and treatment of a series of diseases, many of them chronic and that did not cease to exist in the pandemic. This study aimed to analyze the impact of COVID-19 on computed tomography and magnetic resonance imaging exams based on a trend analysis for these exams in a scenario where the pandemic was absent. This is a transverse study using the Sistema de Informações Ambulatoriais from SUS (SIA/SUS) and simple regression. The results suggest a reduction in both modalities that was more pronounced for computed tomography in the beginning, during COVID-19’s first wave in the country. However, its use as a diagnostic tool resulted in a posterior increase in the number of exams. The potential damage from diagnosis and treatment delay from different diseases due to this issue must be accounted for by the Government to develop public health policies focused on damage control and strengthening the Unified Health System.